EFIKASI SUPLEMENTASI FORMULA TEMPE BENGKUANG TERHADAP KADAR ALBUMIN DAN Z-SKOR BERAT BADAN MENURUT UMUR (BB/U) PADA ANAK GIZI KURANG - Symond, Denas; Oenzil, Fadil; Darwin, Eriyati; Lipoeto, Nur Indrawati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The aim of this study was to determine the efficacy of formulated tempe-yam supplementation on weight for age z-score of underweight children aged 2-4 years. A quasi experiment pre-post test with control group design was applied in this study for four weeks. The intervention group consist of 19 children given formulated tempe-yam 100 g/d; and the control group consist of 19 children given biscuit 100 g/d in Padang Pariaman district, West Sumatera. Data collected included weight, height, and albumin level. Paired t-test was applied for the data analysis. The results of this study found significant differences in albumin level before and after on control group (p<0.05). Then, the results of this study also found significant differences in weight for age z-score before and after on intervention group (p<0.05). Therefore, formulated tempe-yam supplementation as food sumplementation need to be considered for underweight children.Keywords: albumin level, food suplementation, tempe-yam, weight-for age z-score